Speech Genre in Linguistic Variantology (on Material of Speech Genre “Personal Letter”) - T. G. Rabenko (Научный диалог, 2017)
The possibility of speech genre consideration in the paradigm of linguistic variantology is proved. The author argues that the extrapolation of variant-invariant relations in genres studies allows to present a speech genre in the form of the opposition “invariant : variant.” The thesis is that the speech genre invariant is a mental schema (prototype), represented by means of genre-relevant features, integral to the speech modifications of this unit. It is proved that variants of the speech genre are regularly reproducible modifications of the same speech genre. Maintaining identity of illocutionary-intentional, thematic content, formal compositional frameworks, they differ by a series of communicative-pragmatic properties: area of operation, nature of interaction between author and addressee, process of communication (its spatial and temporal characteristics), substrate (e.g. letter on paper or electronic one). Develop theoretical propositions are considered on the material of the variable functioning of the speech genre “personal letter” in different communicative spheres (natural written, electronic, art). The study establishes the invariant features of studied genre (predominant mono-authorship, alter-addressing, dialogism, narrative subjectivity, realism, authenticity, three-part structure) and its variant signs (electronic substrate of network version of a letter; public sphere of communication, formal communication, complex system of addressing letters to the newspaper; artistic letter’s fiction).